O’smir yoshdagi o’quvchilarda shaxs sifatlarining shakllanishi - Yusupov, Q. (SCIENCE and SOCIETY, 2021)
The article presents the socio-psychological foundations of the formation of personality traits in adolescents, as well as provides psychological and pedagogical information about the development of personality in adolescents through the implementation of communication processes corresponding to their age in educational activities.
Keywords: person; personality; adolescence; development; progress; behavior; socialization; crisis; communication; education; activity; objective; subjective; status; work